(untitled) (Vietnam Journal of Community Medicine, 2022)
Objectives: To estimate the distribution, transmission rate, and the risk of transmission of Carbapenem-resistant Enterobacteriaceae (CRE) isolated from newborns patients admitted to the Nghe An Obstetrics and Pediatrics Hospital between June 2022 and July 2022. Methods: A cohort study with screening for colonization with CRE was conducted on 156 newborns under 28 days old admitted to neonatal department, Nghe An Obstetrics and Pediatrics Hospital between June 2022 and July 2022. CRE colonization was determined by culturing of fecal specimens on Carba-smart medium for CRE. Risk factors for CRE transmission were evaluated. Results: The prevalence of CRE infections was 3.2% upon admission and 53.2% at discharge. Fifty percent of patients with negative screening results for CRE were infected during the hospitalized days. K. Pneumoniae agent was the leading cause of transmission. Sex, gestational age, birth weight, respiratory failure, mechanical ventilation, and Oxygen inhalation are factors associated with CRE transmission. Conclusions: The prevalence of CRE infections increased during the hospitalized period. K.Pneumoniae agent was the leading cause of transmission. Gestational age, sex, birth weight, respiratory failure, mechanical ventilation, and oxygen inhalation